STUDI KRITIS TINGKAT KEHALALAN MINUMAN KOMBUCHA - Riswanto, Dody; Rezaldi, Firman (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
The purpose of this study was to measure the alcohol content in the fermented kombucha drink. The alcohol content was tested because consumers of this kombucha drink are the majority of Muslims who require halal standards in food and beverage products. The research method is a laboratory test with a specific treatment design using 2 samples, namely black tea and kecombrang flowers. The results and discussion of this study are that the results of kombucha tests carried out in the laboratory show the results of the ethanol/alcohol content of 0.055 percent. The test results have met the regulatory standards of the Indonesian Ulema Council (MUI) where halal fermented drinks are below 0.5 percent. Thus, the tested fermented kombucha drink has been declared a halal drink and can be consumed by Muslim consumers.